1981
DOI: 10.1136/bmj.282.6277.1656
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic studies in unaffected co-twins of non-insulin-dependent diabetics.

Abstract: twins than controls. After glucose challenge blood glucose, lactate, alamnne, and glycerol concentrations and lactate: pyruvate ratio were increased in the twins. Insulin response was severely impaired, being almost absent in four of the five twins.The non-diabetic members of the discordant noninsulin-dependent diabetic pairs showed noticeable metabolic abnormalities which would later presumably deteriorate to frank diabetes. These findings, taken with the high concordance rate for non-insulin-dependent diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 10 publications
1
31
2
Order By: Relevance
“…In a cross-sectional study (Study 1) changes in glucose tolerance occurred without changes in other intermediary metabolites or insulin. This contrasts with studies of non-diabetic patients at risk of non-insulin-dependent diabetes which showed that these patients can have changes in both glucose and intermediary metabolites [6,7]. The twins who remain non-diabetic did not, as a group, show any changes in either intermediary metabolites or insulin levels; one of these twins from Study i had impaired glucose tolerance.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In a cross-sectional study (Study 1) changes in glucose tolerance occurred without changes in other intermediary metabolites or insulin. This contrasts with studies of non-diabetic patients at risk of non-insulin-dependent diabetes which showed that these patients can have changes in both glucose and intermediary metabolites [6,7]. The twins who remain non-diabetic did not, as a group, show any changes in either intermediary metabolites or insulin levels; one of these twins from Study i had impaired glucose tolerance.…”
Section: Discussioncontrasting
confidence: 66%
“…These observations suggest that clinical diabetes is preceded by detectable metabolic changes presumably due to Beta cell dysfunction. Minor Beta cell dysfunction can be associated with extensive changes in intermediary metabolism other than glucose; such changes have been found in nondiabetic identical twins and children of non-insulin-dependent diabetic patients both of whom were at high risk of developing diabetes [6,7]. Similar changes in intermediary metabolism could occur in twins at risk of insulin-dependent diabetes mellitus.…”
mentioning
confidence: 95%
“…Follow-up questionnaires have been sent in 1981, 1990(Kaprio, 2013, and the twins have been linked to national medical registers (hospital discharge, medication, and cause-of-death data). Information from these registers, hospital charts, and questionnaire surveys were used to identify and classify twins with diabetes and the type of diabetes.…”
Section: The Finnish Twin Cohort Study (Ftcs)mentioning
confidence: 99%
“…If the increased lactate production per fat cell under hyperinsulinemic conditions, as demonstrated in this study, has any relation to the increased risk of type 2 diabetes in individuals with enlarged subcutaneous abdominal fat cell size (58), then it needs to be evaluated in future studies. However, lactate elevation could possibly be a forerunner of or causative factor in (22-24) the development of carbohydrate intolerance and type 2 diabetes (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, epidemiological data have shown that elevated plasma lactate is an independent risk factor for developing type 2 diabetes (11); moreover, in previous studies (12)(13)(14), plasma lactate was either slightly increased or similar in the relatives of type 2 diabetic patients. It is well known that insulin-resistant obese subjects exhibit increased circulating lactate concentrations (15,16).…”
mentioning
confidence: 99%